Hydrogen evolution reaction at extreme pH conditions of copper sulfide micro-hexagons - Karthik S. Bhat; H.S. Nagaraja (Journal of Science: Advanced Materials and Devices, 2020)
Electrochemical hydrogen evolution reaction (HER) using non-precious compounds has gained substantial interest in the development of water electrolyzers. Herein, we report the synthesis of Copper sulfide (Cu2S) micro-hexagons via a hydrothermal method, followed by some of the important physiochemical characterizations and electrochemical measurements towards the HER. Cu2S micro-hexagons could catalyze the HER in both basic (1 M KOH) and acidic solutions (0.5 M H2SO4), corresponding to the extreme pH values of 14 and 0, respectively. As manifested from the polarization curve, Cu2S micro-hexagons required an overpotential of −330 mV and −312 mV to deliver a benchmark catalytic current density of 10 mA cm−2 in basic and acidic solutions, respectively. Furthermore, lower overpotentials are complemented with the prominent long-term stability of 24 h, as evident from chronopotentiometric analysis. The superior electrochemical performance of these Cu2S micro-hexagons demonstrates their promising suitability for water-splitting applications.